2017
DOI: 10.15448/1984-7289.2017.1.25942
|View full text |Cite
|
Sign up to set email alerts
|

About the universality of a concept: is there a financialization of daily life in France?

Abstract: Based on the French case, this article aims to challenge the concept of "financialization of daily life". This notion does not perfectly describe the transformation of money management experienced by French households; compared to other developed countries, their money is kept at a remove from financial markets, particularly as the French retail banking system, built in the 1960s, is designed to "definancialize" and the French welfare state maintains its protective position. The French economy is nonetheless d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…This was originally due to the qualitative nature of the FoEL literature, using single-sited ethnographies and interviews, with the vast majority of studies conducted in the UK and the US. These were later complemented by studies outside of these contexts, such as France (Lazarus, 2017), Italy (Di Feliciantonio, 2016), the Czech Republic (Samec, 2018), Poland (Lewicki, 2014), Hungary (Pellandini-Simanyi et al, 2015), Chile (Gonzalez, 2015), Israel (Ailon, 2019;Weiss, 2015), Argentine (Fridman, 2017), China (Maso, 2015), and Singapore (Lai, 2016(Lai, , 2017, among others.…”
Section: Geographies Of Financial Subjectivitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This was originally due to the qualitative nature of the FoEL literature, using single-sited ethnographies and interviews, with the vast majority of studies conducted in the UK and the US. These were later complemented by studies outside of these contexts, such as France (Lazarus, 2017), Italy (Di Feliciantonio, 2016), the Czech Republic (Samec, 2018), Poland (Lewicki, 2014), Hungary (Pellandini-Simanyi et al, 2015), Chile (Gonzalez, 2015), Israel (Ailon, 2019;Weiss, 2015), Argentine (Fridman, 2017), China (Maso, 2015), and Singapore (Lai, 2016(Lai, , 2017, among others.…”
Section: Geographies Of Financial Subjectivitiesmentioning
confidence: 99%
“…First, they showed that neoliberal discourse is less successful in producing neoliberal subjects in some contexts, while more successful in others. Several studies documented what we called ‘reluctant financialisation’: resistance to financialised subjectification and governance mechanisms (Coppock, 2013; Di Feliciantonio, 2016; Fields, 2017; Gonzalez, 2015; Montgomerie and Tepe-Belfrage, 2017, 2019; Weiss, 2015) or partial adoption of some elements of the financialised mind-set, yet in appropriated and contested ways (Gonzalez, 2015; Hillig, 2019; Lai, 2016, 2017; Langley, 2014; Lazarus, 2017; Lehtonen, 2017; Pellandini-Simanyi et al., 2015; Samec, 2018).…”
Section: The Financialisation Of Everyday Life: the Ideal Financialised Subject Vs The Lived Experience Of Financialisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we believe that French theoretical traditions and ways of assessing credit issues are key to understanding the French path to financialization. Unlike in Anglo-American countries, the financialization of savings, personal insurance, and pension plans is still low-though it is growing-and has yet to emerge as a political issue (Lazarus, 2017). For now, the effects of financialization are mostly considered through the prism of the destabilization of work that it produces (Chambost, 2013), but not through the financialization of daily life.…”
Section: Credit and Financializationmentioning
confidence: 99%
“…On one hand, people could have been equipped and trained with the financial calculative technologies (formulas, devices, algorithms), but their actual uses of them did not match with the expected idea or goal. On the other hand, the fact that people find creative and adaptive uses of financial products, services, and techniques in their social lives also tells us that the financialization of everyday life (Martin, 2002;Lazarus, 2017) is not necessarily a process through which finance erodes social bonds of communities or exploits their social capital as assumed by feminist and Marxist critical approaches (see Rankin, 2011;Roberts, 2014;Federici, 2014;Green and Estes, 2019). In fact, those effects of financial governmentality that I illustrated through cases studies and conceptualized as overflows, excess or productive engagements Bank W is one of the most important microfinancial institutions in Colombia with more than 30 years in business, the third highest profit rate among microcredit institutions (Asobancaria, 2017), and the second bigger share at national level among private MFIs (nearly 5% of total market share).…”
Section: Discussionmentioning
confidence: 99%